cogsworth: A Gala of COSMIC Proportions Combining Binary Stellar Evolution and Galactic Dynamics - Tom Wagg; Katelyn Breivik; Mathieu Renzo; Adrian M. Price-Whelan (The Astrophysical Journal Supplement Series)
We present cogsworth , an open-source Python tool for producing self-consistent population synthesis and galactic dynamics simulations. cogsworth allows users to (1) sample a population of binaries and star formation history, (2) perform rapid (binary) stellar evolution, (3) integrate orbits through the galaxy, and (4) inspect the full evolutionary history of each star or compact object, along with their positions and kinematics. It supports postprocessing hydrodynamical zoom-in simulations for more realistic galactic potentials and star formation histories, accounting for initial spatial stellar clustering and complex potentials. Alternatively, several analytic models are available for galactic potentials and star formation histories. cogsworth can also transform the intrinsic simulated population into an observed population using dust maps, bolometric correction functions, and survey selection functions. We provide a detailed explanation of the functionality of cogsworth and demonstrate its capabilities through a series of use cases: (1) we predict the spatial distribution of compact objects and runaways in both dwarf and Milky Way–like galaxies; (2) using a star cluster from a hydrodynamical simulation, we show how supernovae can change the orbits of stars in several ways; and (3) we predict the separation of disrupted binary stellar companions on the sky and create a synthetic Gaia color–magnitude diagram. We use cogsworth to demonstrate that both binarity and the galactic potential have a significant impact of the present-day positions of massive stars. We designed cogsworth and its online documentation to provide a powerful tool for constraining binary evolution, but also a flexible and accessible resource for the entire community. https://github.com/TomWagg/cogsworth https://cogsworth.readthedocs.io/en/latest/